Representasi Kegagalan Cinta dan Kriminalitas dalam Novel Seribu Wajah Cinta Karya Fredy S. - Rizam, Masyithah Maghfirah; Effendy, Moh Hafid (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Literary works are able to describe the reality outside of the human being exactly as it is. The novel of Seribu Wajah Cinta by Fredy S. is a form of popular literature. Popular literature restates records of life in hope that the reader will get to know his experiences again so that they feel comforted, because someone has told his experience. The research method uses a qualitative approach with the researcher acting as a key instrument. Data collection was carried out by taking steps, carrying out intensive reading, recording data, coding the parts of the novel that were appointed as data, analyzing, and interpreting the data to find representations of broken relationship and criminality in the novel of Seribu Wajah Cinta by Fredy S. shows the broken relationship and criminality which is a reflection of daily life.